2011
DOI: 10.1007/s10157-011-0487-0
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of mizoribine in adult recipients of renal transplantation

Abstract: The present findings suggested that not only the rate of renal excretion but also the extent of intestinal absorption of mizoribine is responsible for the large interindividual pharmacokinetic variability of the drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…2) Recently, we have reported that the variability of bioavailability (F) is one of the causes of the interindividual pharmacokinetic variability of mizoribine, an immunosuppressive agent. 3,4) That is, we analyzed the serum concentration data of mizoribine in adult and pediatric recipients of renal transplantation using a nonlinear mixed effect model (NONMEM) program. We found a significant positive correlation between CL/F and the apparent volume of distribution (V/F) in both studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Recently, we have reported that the variability of bioavailability (F) is one of the causes of the interindividual pharmacokinetic variability of mizoribine, an immunosuppressive agent. 3,4) That is, we analyzed the serum concentration data of mizoribine in adult and pediatric recipients of renal transplantation using a nonlinear mixed effect model (NONMEM) program. We found a significant positive correlation between CL/F and the apparent volume of distribution (V/F) in both studies.…”
Section: Introductionmentioning
confidence: 99%
“…We found a significant positive correlation between CL/F and the apparent volume of distribution (V/F) in both studies. 3,4) Since the plasma protein binding of mizoribine is negligible, the systemic clearance (CL) of the drug may not be correlated with the volume of distribution (V). In addition, mizoribine is not subjected to hepatic firstpass metabolism, and is exclusively excreted into the urine as the unchanged form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently performed population pharmacokinetic analysis of mizoribine in adult and pediatric recipients of renal transplantation with a nonlinear mixed effects model (NONMEM) program, and reported that the pharmacokinetics of mizoribine was described well by the 1-compartment model with absorption lag time (ALAG) and rst-order absorption. 7,8) In addition, there was a positive correlation between the apparent volume of distribution (V/F) and oral clearance (CL/F).…”
Section: Regular Articlementioning
confidence: 99%
“…Therefore, the positive correlation between V/F and CL/F can be due to the variability of F. The variable F of mizoribine reflects the extent of intestinal absorption of the drug, because there is no rst-pass metabolism of mizoribine in the liver and intestine. 7,8) On the other hand, we previously performed population pharmacokinetic analysis of mizoribine in healthy adult men. 9) In this analysis, we assumed that the variability of F was negligible in healthy subjects, and omitted the correlation between V/F and CL/F.…”
Section: Regular Articlementioning
confidence: 99%